Spite in Litigation - Wladislaw Mill; Jonathan Stäbler (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper studies how litigation and settlement behavior is affected by agents motivated by spiteful preferences under the American and the English fee-shifting rule. We conduct an experiment and find that litigation expenditures and settlement requests are higher for more spiteful participants. The relative increase in litigation expenditures due to spite is more pronounced under the American fee-shifting rule. We further find that the expected payoff for more spiteful societies is lower than for less spiteful societies. This effect is particularly pronounced for low-merit cases under the English rule compared to a constant cost under the American rule.
Keywords: K41; C72; C91; D91; 330; spite; litigation; settlement; experiment; English rule; American rule